Role Of Management Information Systems In Decision-Making Effectiveness Among Departments Ministry Of Youth And Sports And Schools Directors From Employees Perspective - Ghazwan Azeez Mohsen; Humam Ismail Hussein; Alhussein Hamza Shaalan (Musamus Journal of Physical Education and Sport (MJPES), 2026)
This study aimed to identify level of implementation of management information systems (MIS) in departments of Ministry of Youth and Sports and School Activities from perspective of its employees. Study scope was as follows Human scope employees in departments of Iraqi Ministry of Youth and Sports; Temporal scope from April 9, 2025, to June 11, 2025; Spatial scope offices of employees in departments of Ministry of Youth and Sports. The researchers defined their population as all employees in departments of Iraqi Ministry of Youth and Sports, totaling 530 employees distributed across 10 departments. A 50% sample was selected, resulting in a research sample of 265 employees. Sample was selected using simple random sampling and then divided into three main subgroups. The researchers recommended necessity of developing MIS in departments of Ministry of Youth and Sports to ensure data accuracy, timeliness, and integration across different departments. They also recommended focusing on simplifying technical and organizational procedures to facilitate employees’ access to information in a timely manner and in accordance with nature of their tasks and responsibilities. Enhancing managers’ reliance on management information systems (MIS) outputs when making decisions, and reducing decisions based on personal judgment unsupported by data. Organizing training courses for employees and administrators on how to use MIS effectively to support decision-making process.